Synthesis of alumina-CaO-KI catalyst for the production of biodiesel from rubber seed oil [Sintesis mangkin alumina-CaO-KI untuk penghasilan biodiesel daripada minyak biji getah] - Abdul Razak, Zainal Kifli; Shahida Hanum, Kamarullah; Siti Norhafiza, Mohd Khazaai; Gaanty Pragas, Maniam (Universiti Kebangsaan Malaysia, 2018)
In this research, biodiesel was produced by transesterification of rubber seed oil with methanol catalyzed by three types of alumina-supported catalyst. The catalysts were Al2O3 -CaO, Al2O3 -KI, and Al2O3 -CaO-KI. The catalysts were prepared by heating a mixture of alumina and the corresponding salt in a furnace at 700 oC. Transesterification reactions were carried out at 65 °C using a mixture of rubber seed oil: methanol of mass ratio 1:9 with different catalyst loadings between 0 and 3.5%. The optimum catalyst loading was at 2.0% for all types of catalyst and Al2O3 -CaO-KI gave the highest yield (91.6%) followed by Al2O3 -KI (90.7%) and Al2O3 -CaO (63.5%). The catalyst Al2O3 -CaO-KI also gave high biodiesel yields over a wider range of catalyst loadings compared to the other two catalysts. Reactions were also carried out at different temperatures (25, 40 and 65°C). It was observed that the yield increased drastically with increasing reaction temperature. At all temperatures the Al2O3 -CaO-KI catalyst gave the highest yield. Therefore, the study showed that among these three catalysts the most productive was Al2O3 -CaO-KI, (100:30:35).